Fuzzy Proportional-Derivative Based Robot Arm Control for Object Transfer. Issue 1 (1st April 2022) - Chen, Shouyan; Yu, Huaxin; Tan, Zhifeng; Huang, Junfeng; Zhou, Danting; Li, Haozhuo
Abstract: With the development of robot technology, humanoid robot and human-robot interaction are gradually playing a more and more important role in our society. At present, the arm control of humanoid intelligent robot has become one of the hot research issues in the field of robot. This paper proposes a fuzzy based NAO robot hand control method to reduce the vibration and increase position accuracy during object transferring between NAO robot and human. The 5-DOF kinematics model of NAO robot right arm is first established. Motion path of the NAO robot arm during human-robot interaction is planned and conducted in Matlab and reality. The impact of control period, joint speed and trajectory error on vibration is observed and discussed. Based on the discussion, the fuzzy-PD control method is proposed. Experiments result indicates that the proposed Fuzzy-PD control method can reduce vibration and trajectory error, which can benefit the smooth motion control process of the NAO robot arm receiving objects in the process of human-robot interaction.